Pengaruh Work Environment dan Self Efficacy Terhadap Turnover Intention Karyawan di Hotel AP Premier Batam - Santia, Ulva; Adrian, Arif (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
This study looks at how environment of work and self efficacy affect employee turnover intention at AP Premier Hotel Batam. This research purposes is to reveal the environment of work and self efficacy impact on turnover intention at AP Premier Hotel Batam. This research utilized methods by quantitative through an approach of causal associative to examine 47 respondents. The research results are work environment and self efficacy have no significant effect on employee turnover intention at AP Premier Hotel Batam.